(untitled) (International Journal of Financial, Administrative and Economic Sciences, 2026)
Purpose: This empirical study examines the relationship between strategic entrepreneurship and institutional performance within the Saudi Public Investment Fund (PIF), with a particular focus on the mediating role of strategic leadership. The study addresses a gap in the literature by explaining how entrepreneurial orientations are translated into measurable performance outcomes in sovereign wealth funds. Design/methodology/approach: A quantitative cross-sectional research design was employed. Data were collected from a stratified random sample of 337 professional employees at different organizational levels within PIF. Strategic entrepreneurship was modeled as a second-order construct comprising entrepreneurial mindset, entrepreneurial leadership, entrepreneurial culture, strategic resource management, and creativity and innovation application. Institutional performance was measured using the Balanced Scorecard dimensions, while strategic leadership was conceptualized as a reflective construct. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4, supported by bootstrapping procedures. Findings: The results indicate a significant positive effect of strategic entrepreneurship on institutional performance. Strategic leadership was found to partially mediate this relationship, confirming its role as a key mechanism through which entrepreneurial capabilities enhance performance. The measurement and structural models demonstrated strong reliability, validity, and explanatory power. Originality/value: This study extends strategic entrepreneurship and leadership theories to the context of sovereign wealth funds and provides empirical evidence on the mediating role of strategic leadership in enhancing institutional performance. Practical implications: The findings offer actionable insights for policymakers and executives in sovereign investment institutions, emphasizing the importance of developing strategic leadership capabilities and fostering entrepreneurial practices to improve institutional performance.